Kriptografi Klasik Menggunakan Modifikasi Metode Affine Ciphers - Harahap, Anggi Syahadat (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2023)
Cryptography is the science or art to maintain the security of messages that include the security aspects such as confidentiality, data integrity and authentication. One method that is able to encrypt messages Affine Ciphers modified. Plaintext encrypted with Affine Cipher using the equation E (P) = (ax + b) mod m, where m is the size of the alphabet, a is an integer relatively prime to m, b is the number of shifts, x is the plaintext is converted to an integer of 0 to m-1 in accordance with the order of the alphabet, E (P) is ciphertext that is converted to an integer of 0 to m-1 in accordance with the order of the alphabet. Affine Ciphers ciphertext is decrypted by using the equation D(E(P))=a-1(E(P)-b) mod m in order to obtain the plaintext.